European Monetary Integration / From the European Monetary System to Economic and Monetary Union - Gros Daniel; Thygesen Niels (Longman, 1998)
An essential reading for all students of European monetary integration and international macroeconomics, as well as anybody with a professional interest in European economics. Introduction, A Brief History of European Monetary Integration, The Beginning: from the European Payments Unions to the Snake, The Making of the European Monetary System, The European Monetary System, The European Monetary System and the ecu, Analytical Issues: A Critical Appraisal of the EMS - 1979-92, Lessons from a Failed Transition? The Speculative Attacks of 1992-5, From the Ecu, Analytical Issues: a Critical Appraisal of the EMS - 1979-92, Lessons from a Failed Transition? The Speculative Attacks of 1992-5, From the Ecu to the Euro, The Economics of Monetary Union, Why Monetary Union? Costs and Benefits of EMU, The Relationship between Economic and Monetary Integration: EMU and National Fiscal Policy, EMU and the Global Monetary System, Towards Monetary Union, Agreeing on EMU: From Political Initiatives to the Delors Report and the Maastricht Treaty, After Maastricht: Concrete Steps towards Monetary Union, The European System of Central Banks and Price Stability, Index.